TRADISI DOA SOR’O PADA MASYARAKAT NELAYAN DI DESA ROMPO KECAMATAN LANGGUDU KABUPATEN BIMA NUSA TENGGARA BARAT - Anggrianingsih, Heni (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Rompo village is one of the villages of the twelve villages in the subdistrict administration Langgudu, Bima, NTB.Desa Rompo which have the greatest potential of the fishery, so that livelihood as a fisherman. Sea as the source of people's lives. From the above discussion, in this study the problem to be examined is defined as follows: How does the function of this tradisi doa sor’o Prayer to people's lives Rompo village. This study was conducted to determine the function of Sor Prayer Tradition. This research was conducted using qualitative methods, which were analyzed by Marcel Mauss theory and principle Giving Ceremony theory Bersaji W Robertson Smith. The results showed that the tradition of this prayer has meaning Sor'o how honoring ancestors or ruler of the sea, called the Inna Rice, by doing this tradition of blessing the people get this, people do a ceremony with the casualties of a cow as a tribute to Inna Nasi and function Tradisi Doa Sor’o doing so strengthen keyakina, creating peace, solidarity, social integration, and the welfare of this keluarga.tradisi is still maintained /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Inna Nasi and Tradisi Doa Sor' o